Unpacking the ‘‘skill – cross-cultural competence" mechanisms: Empirical evidence from Chinese expatriate managers - Wang, D.; Feng, T.; Freeman, S.; Fan, David; Zhu, C. (Pergamon, 2014)
International management (IM) literature identifies several important skill sets (namely, self-maintenance, perceptual, interpersonal, language and communication skills) that are important for expatriates’ cross-cultural management. However, how skills influence each other and work synergistically towards expatriate competence has not been well examined. Based on the theoretical perspectives of learning, social dynamics and the IM stream, we develop an integrative model to investigate the joint effects of skills on cross-cultural competence (CCC), by surveying and interviewing Chinese expatriate managers. We find that self-maintenance skills, interpersonal skills, and language skills do not relate to CCC directly, while perceptual skills contribute to CCC mainly through communication skills. Our study demonstrates that competence goes beyond understanding local culture and lies in the ability to effectively interact and communicate within the host context. This study contributes to expatriate literature not only by revealing the skill – CCC mechanisms, but also by extending knowledge into an emerging market context which provides theoretical and practical guidance for competence-building of expatriates from China.